Effect of Microgroove Structure in PDMS-Based Silicone Implants on Biocompatibility - Chen, Yao; Zhou, Xin; Huang, Shuqing; Lan, Yujie; Yan, Rongshuai; Shi, Xiaohua; Li, Xiang; Zhang, Yiming; Lei, Zeyuan; Fan, Dongli (Frontiers in Bioengineering and Biotechnology, 2022)
Capsule and capsule contracture around implants are important concerns in a clinic. The physical topology of the material surface regulates the formation of the capsule, but the specific regulatory mechanism is unclear. In this study, four types of silicone implant materials with different microgroove structures (groove depths of 10 and 50 μm and widths of 50 and 200 μm) were constructed using lithography to form different gradient surface topologies. Mass spectrometry, Cell Counting Kit-8, 5-ethynyl-2′-deoxycytidine (EdU), enzyme-linked immunosorbent assay, western blot, immunofluorescence, and immunohistochemistry were used to explore the changes in protein adsorption, cell adhesion, cell proliferation, and collagen deposition on the surface of the materials. At the same time, RNA-seq was used to detect transcriptome differences caused by different structures. Furthermore, collagen deposition and capsule formation were observed in the rats. The groove structure was observed to significantly increase the surface roughness of the material. The deeper groove and the narrower width of the polydimethylsiloxane would increase the surface roughness of the material and the surface water contact angle but reduce the total amount of adsorbed protein in the first two hours. In vitro cell experiments revealed that microtopology affected cell proliferation and adhesion and regulated collagen secretion. Further analysis indicated the deeper and narrower groove (group 50–50) on the surface of the material caused more evident collagen deposition around the material, forming a thicker envelope. Surface roughness of the material was thus related to collagen deposition and envelope thickness. The thickness of the envelope tissue around smooth materials does not exceed that of the materials with surface roughness. In conclusion, the narrower and deeper grooves in the micron range exhibited poor histocompatibility and led to formation of thicker envelopes around the materials. The appropriate grooves can reduce envelope thickness.